Adverse reaction; patent blue turning patient blue. (30th November 2012) - Joshi, Meera; Hart, Matthew; Ahmed, Farid; McPherson, Sandy
Abstract : The authors report a severe anaphylactic reaction to Patent Blue V dye used in sentinel node biopsy for lymphatic mapping during breast cancer surgery to stage the axilla. Patent Blue dye is the most widely used in the UK; however, adverse reactions have been reported with the blue dye previously. This case highlights that reactions may not always be immediately evident and to be vigilant in all patients that have undergone procedures using blue dye. If the patients are not responding appropriately particularly during an anaesthetic, one must always think of a possible adverse reaction to the dye. All surgical patients should give consent for adverse reactions to patent blue dye preoperatively. Alternative agents such as methylene blue are considered.